Transformative management education : the role of the humanities and social sciences - Landfester, Ulrike, 1962-; Metelmann, Jörg (Routledge advances in management and business studies., 2019)
"Due to the recent global financial crises, academic business schools have come in for much criticism, having, in the eyes of the public, failed in their responsibility to society by teaching future managers only how to increase their personal gain without any consideration as to their actions' social and cultural consequences. Realising that there is a pressing need to innovate their educational offers accordingly, business schools are beginning to turn to the humanities and social sciences to improve on the understanding and thus the teaching of management. This book is the result of an empirical study conducted at eight academic business schools that either already practise or are beginning to practise linking management education to the humanities and social sciences. Gathered mostly in interviews our research team conducted during site visits to these schools, the material presented shows three major fields of concern: how to shift the focus from instrumental to transformative learning, how to reframe the concept of disciplinary subject matter towards a more relational understanding of knowledge--especially in the light of the impact digitalisation is having on education--and how to address the organisational, as well as the political consequences of management education turning towards the inclusion of the humanities and social sciences strategically."- Resumé vydavatel